DIVERSITY OF RURAL TOURISM PRODUCTS AND CHALLENGES OF RURAL TOURISM DEVELOPMENT IN KOTA MARUDU, SABAH - Jemmy Amanda Sipatau; Jabil Mapjabil; Ubong Imang (Journal of Islamic, Social, Economics and Development, 2020)
Kota Marudu has a variety of products with the potential to be developed as unique and attractive rural tourism attractions, especially in terms of its beautiful nature and cultural heritage. Rural tourism offers a variety of attractions and local products, such as ecotourism and agrotourism, as well as the culture and heritage of local communities. This study examines the diversity of rural tourism products in Kota Marudu. The variety of products is classified into three main features, namely physical attractions, cultural attractions, and events, as well as other attractions. The variety of products is also divided into two parts, namely those developed by local communities and those operated by certain organisations or departments. The aspects of challenges and problems in developing rural tourism products are also examined in this paper. In the context of Kota Marudu, a study of rural tourism development needs to be undertaken to identify the diversity of tourism products that can be potentially developed, and to examine the challenges and problems toward such efforts. In short, various initiatives and policies need to be carried out practically and holistically so that rural tourism in this district continues to be developed and remains competent.